Principles and philosophies, experiences and challenges associated with undertaking otorhinolaryngologic surgical practices and procedures in COVID-19 pandemic - Hernot, Sharad; Pandey, Apoorva Kumar; Kaintura, Madhuri; Bhardwaj, Aparna; Anjum, Fatma; Kala, Sonal; Arora, Kanika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: To highlight the changes, challenges, and safety recommendations associated with surgical management of a patient which were practiced effectively at our institute during the pandemic and share our experience. Methods: This retrospective observational descriptive study conducted between 25th March 2020 and 31st October 2020 constitutes of following points covering various aspects of surgical management of patient such as- general precautions followed by otrorhinolaryngologist while doing OPD surgical procedures, while doing endoscopy, in every major operative elective or emergency surgical procedure. This study also mentions focussed considerations for specialised surgical procedures like otology surgeries, endoscopic sinus and skull base surgeries, airway surgeries, tracheostomy, head and neck carcinoma etc. Results: Of the 342 cases operated between 25th March 2020 and 31st October 2020 during this pandemic, 69 nasal surgeries, 83 ear surgeries, 37 throat surgeries, 37 head and neck surgeries, 26 oesophagoscopies, 17 bronchoscopies, 63 tracheostomies, and 10 cases of maxillofacial trauma were performed. 983 patients were taken up for endoscopic examination of the mucosa of the head and neck in OPD as an office-based procedure. Conclusions: Through this study, we suggest a safety and recommendations procedural framework to be followed while managing surgical patients in a way to minimise the cross transmission of virus.